The tunnel versus medial versus lateral approach in laparoscopic right hemicolectomy in colon cancer: A retrospective study - Leesa Misra,; Mahesh Kumar Sethi,; Manash Ranjan Sahoo,; Preeti Kumari Gond,; Kallol Kumar Das Poddar, (Asian Journal of Medical Sciences, 2023)
Background: Laparoscopic right hemicolectomy for the right-side colon cancer is well-established and proven to be better than the open approach in terms of post-operative and overall hospital stay. Laparoscopic right hemicolectomy can be done by lateral to medial approach (LA), medial to lateral approach (MA), or tunnel/IRETA approach (TA). No previous study has been conducted to compare the clinical outcomes of all three approaches and the superiority of one approach over the other is still debatable. Aims and Objectives: This retrospective study was conducted to compare all three approaches and to find the ideal one to practice. Materials and Methods: This is a retrospective cohort study carried out to analyze 86 patients who were admitted to the department of General Surgery from March 2015 to December 2021 with a diagnosis of the right-side colon cancer and underwent laparoscopic right hemicolectomy with either of these three approaches. A total of 29 patients had operated with lateral to medial approach (LA), 29 patients with medial approach (MA), and 28 with tunnel (TA) approach. The patient’s baseline demographics, perioperative parameters, and post-operative outcomes were compared. Results: Intraoperative blood loss was significantly lower in the medial to lateral approach and tunnel approach. Duration of surgery was less in the medial to lateral approach as compared to the other two approaches and was statistically significant. R0 resection, lymph node dissection, intraoperative and post-operative complications, morbidity, mortality, and conversion to open were similar in all three groups. Conclusion: Laparoscopic medial to lateral to medial to lateral approach is feasible and safe and should be preferred approaches in laparoscopic right hemicolectomy.